First report on a novel Nigrospora sphaerica isolated from Catharanthus roseus plant with anticarcinogenic properties. Issue 4 (14th June 2017) - Ayob, Farah Wahida; Simarani, Khanom; Zainal Abidin, Nurhayati; Mohamad, Jamaludin
Summary: This paper reports on the vinca alkaloid produced by a novel Nigrospora sphaerica isolated from Catharanthus roseus . Through liquid chromatography–mass spectrometry (LCMS), only the crude mycelia extract of this fungus was positive for determination of vinblastine. This vinca alkaloid was then purified by using high‐performance liquid chromatography (HPLC) and tested for cytotoxicity activity using MTT assays. The breast cell line cancer (MDA‐MB 231) was treated with a purified vinblastine which was intracellulary produced by N. sphaerica . The purified vinblastine from extracted leaf of C. roseus was used as a standard comparison. A positive result with a value of half maximal inhibitory concentration (IC50 ) of > 32 μg ml −1 was observed compared with standard (IC50 ) of 350 μg ml −1 only. It showed that a vinblastine produced by N. sphaerica has a high cytotoxicity activity even though the concentration of vinblastine produced by this endophytic fungus was only 0.868 μg ml −1 . Abstract : This paper reports on the vinca alkaloid produced by a novel Nigrospora sphaerica isolated from Catharanthus roseus . The breast cell line cancer (MDA‐MB 231) was treated with a purified vinblastine, which intracellularly produced by N. sphaerica . It showed that a vinblastine produced by N. sphaerica has a high cytotoxicity activity.